Transformasi Model Bisnis Ritel Tradisional ke Omni-Channel: Analisis Dinamis terhadap Perilaku Switching Konsumen, Keseimbangan Pasar dan Permintaan Agregat - Syafitria, Agnes Alzena (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to analyze how the transformation of traditional retail business models to omni-channel models can influence consumer switching behavior, market equilibrium, and aggregate demand. The research method uses descriptive qualitative analysis, with primary and secondary data sources, which are then analyzed through an interactive qualitative model. The results of the study reveal that the adoption of the omni-channel model significantly drives an increase in consumer switching behavior from traditional channels to digital channels. Key factors driving switching include ease of access, service integration, and consistency in the shopping experience. This transformation leads to changes in market structure, where retail players that can adapt experience increased competitiveness, while conventional retail faces declining demand. Overall, aggregate demand shows an increase along with wider market access and improved consumer experiences. The conclusion of this study emphasizes that the shift to an omni-channel business model is not just a trend but a strategic necessity in the face of digital disruption. Retail players are required to continuously innovate to meet the increasingly complex and dynamic expectations of consumers.